A Global Trend of the Electronic Supply Chain Management (e-SCM) Research: A Bibliometric Analysis - Aidi Ahmi; Suzari Abdul Rahim; Hany Elbardan (International Journal of Supply Chain Management, 2018)
Research about electronic supply chain management (e-SCM) has been initiated on 2000, during the advancement of the internet and the information and communication technology (ICT). Since then, e-SCM attracted the attention of many researchers and various studies were conducted. This study aims at drawing the trends of the e-SCM research using bibliometric analysis of all the up to date e-SCM publications that has been indexed in Google Scholar and offer some research ideas in e-SCM. E-SCM related keywords have been used to search in the Google Scholar database. Analysed parameters include year of publication, publication type, language of publication, citation analysis, title analysis, and authorship patterns. The findings show that the first publication on e-SCM was in 2000 and the e-SCM publications reached its peak during 2009. Journal articles type is the most common type that has been published compared to conference paper and other publication types. English language is the dominant publication language. Three publications on e-SCM have been cited more than 100 times. This study also found that the word analysis and study are the common words used in the title of the publications and most of the publications in e-SCM have been written by a single author.